2003
DOI: 10.1210/me.2003-0141
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Shock Protein 90-Targeting Drug Cisplatin Selectively Inhibits Steroid Receptor Activation

Abstract: Cisplatin is an antineoplastic drug that binds to DNA, thereby inhibiting cell division and tumor growth. Cisplatin may also disrupt the function of some proteins, including heat shock protein 90 (Hsp90). We report that cisplatin dose-dependently inhibited transcriptional activity of the androgen receptor and the glucocorticoid receptor (GR) in transient reporter assays. A truncated, hormone-independent GR was only partially inhibited at significantly higher doses of cisplatin. Cisplatin treatment of neuroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 80 publications
2
49
0
Order By: Relevance
“…The ligand-binding ability of exogenously expressed GR was shown to be significantly inhibited by cisplatin, which led to the hypothesis that cisplatin-induced inhibition of Hsp90 only affects a fraction of Hsp90 client proteins, for example, steroid receptors (Rosenhagen et al, 2003). Our ligand-binding assay performed in LNCaP cells with endogenous expression of AR showed that cisplatin only caused a slight reduction in the ligand-binding activity of this receptor.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The ligand-binding ability of exogenously expressed GR was shown to be significantly inhibited by cisplatin, which led to the hypothesis that cisplatin-induced inhibition of Hsp90 only affects a fraction of Hsp90 client proteins, for example, steroid receptors (Rosenhagen et al, 2003). Our ligand-binding assay performed in LNCaP cells with endogenous expression of AR showed that cisplatin only caused a slight reduction in the ligand-binding activity of this receptor.…”
Section: Discussionmentioning
confidence: 85%
“…It should be noted that our cell fractionation experiment (Figure 3c) did not reveal a subcellular redistribution of Ser81 phosphorylated AR at early time points in response to genotoxic stress (data not shown). The activity of exogenously expressed AR and glucocorticoid receptor (GR) in neuroblastoma cells has been demonstrated to be inhibited in response to cisplatin, and for the GR, this was linked to the cisplatin-induced inhibition of the molecular chaperone Hsp90 (Rosenhagen et al, 2003). As the AR is an Hsp90 client protein (Georget et al, 2002), it is possible that loss of AR activity and loss of protein expression at later time points, in response to cisplatin, could be related to a cisplatin-induced inhibition of Hsp90 in LNCaP cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, effects of dicoumarol, 17AAG, and novobiocin were somewhat variable when compared with each other. However, differences in inhibitory effect profiles are common among Hsp90 inhibitors and may reflect differences in mechanisms of action on the Hsp90 molecule (33).…”
Section: Aacrjournalsorg Downloaded Frommentioning
confidence: 99%
“…6c). Half-maximal inhibition of binding occurs with Ϸ100 M NB and 1 M CP, comparable to their apoptotic potencies (36,37).…”
Section: Resultsmentioning
confidence: 84%
“…However, CP and NB bind to the C terminus of HSP90 both in vitro and in vivo (35)(36)(37). CP binds HSP90, decreasing the transcriptional activity of androgen and glucocorticoid receptors although not affecting other HSPregulated proteins, such as the phosphokinases Raf-1, Lck, and c-Src (37).…”
Section: Discussionmentioning
confidence: 99%